Peranan Sektor Pertambangan dalam Pembangunan Ekonomi Implikasinya pada Lingkungan - Setiawan, Imam (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The region's mining industry is one endeavor aimed at enhancing economic conditions. To be sure, a major boost to economic growth can come from involving the mining industry as one of the tactics to strengthen the local economy. The aim of this study is to determine the degree to which environmental sustainability is taken into consideration during the planning and execution of mining operations, as well as the environmental repercussions that these activities produce in the context of economic development. The research methodology used in this study is qualitative normative juridical descriptive research. Literature reviews from books and journals are used in the data collection method. According to the study's findings, mining operations can harm nearby ecosystems by degrading the soil, contaminating water supplies, and emitting harmful air pollutants. Human health as well as the survival of the local flora and wildlife may be seriously impacted by mining waste and the pollution that results from it. Innovation and green technologies in the mining industry can assist lessen harmful effects on the environment. Keywords: Economics, Environment, Mining.